2018
DOI: 10.1159/000489273
|View full text |Cite
|
Sign up to set email alerts
|

Endotracheal Intubation and In-Hospital Mortality after Intracerebral Hemorrhage

Abstract: Background: Many patients with acute intracerebral hemorrhages (ICHs) undergo endotracheal intubation with subsequent mechanical ventilation (MV) for “airway protection” with the intent to prevent aspiration, pneumonias, and its related mortality. Conversely, these procedures may independently promote pneumonia, laryngeal trauma, dysphagia, and adversely affect patient outcomes. The net benefit of intubation and MV in this patient cohort has not been systematically investigated. Methods: We conducted a large s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 35 publications
7
10
0
Order By: Relevance
“…We identified several factors associated with prognosis in the multivariable logistic regression analysis, including age > 65 years, intubation, hypertension, diabetes, apnea, SOFA score, glucose level, WBC count, and GCS on admission. These results are in line with previous findings that age (34), intubation (35), GCS on admission, severity of illness (4), hypertension, diabetes (36), apnea, high blood glucose levels (6), and WBC count (37) are significant predictors of the outcomes in patients with various HBI.…”
Section: Discussionsupporting
confidence: 92%
“…We identified several factors associated with prognosis in the multivariable logistic regression analysis, including age > 65 years, intubation, hypertension, diabetes, apnea, SOFA score, glucose level, WBC count, and GCS on admission. These results are in line with previous findings that age (34), intubation (35), GCS on admission, severity of illness (4), hypertension, diabetes (36), apnea, high blood glucose levels (6), and WBC count (37) are significant predictors of the outcomes in patients with various HBI.…”
Section: Discussionsupporting
confidence: 92%
“…Mechanical ventilation after tracheotomy or endotracheal intubation may prevent OSA-related hypoxia. However, a previous study have reported that in acute spontaneous ICH patients, endotracheal intubation and mechanical ventilation were associated with increased risk of hospital-acquired pneumonia and inhospital mortality [40]. Consistently, in the present study, we found that the proportions of patients with tracheotomy and endotracheal intubation were higher in the poor outcome group.…”
Section: Discussionsupporting
confidence: 91%
“…Mechanical ventilation after tracheotomy or endotracheal intubation may prevent OSA-related hypoxia. However, a previous study reported that in acute spontaneous ICH patients, endotracheal intubation and mechanical ventilation were associated with an increased risk of hospital-acquired pneumonia and in-hospital mortality (40). Consistently, in the present study, we found that the proportions of patients with tracheotomy and endotracheal intubation were higher in the poor outcome group.…”
Section: Discussionsupporting
confidence: 91%